Adsorption and charge transfer interactions of bi-isonicotinic acid on Ag(111) - Temperton, Robert H.; Gibson, Andrew J.; Handrup, Karsten; O'Shea, James N. (American Institute of Physics, 2017)
The adsorption and charge transfer dynamics of the organic molecule bi-isonicotinic acid (4,4′-dicarboxy-2,2′-bipyridine) on single crystal Ag(111) has been studied using synchrotron radiation-based photoemission, x-ray absorption and resonant core spectroscopies. Measurements for multilayer and monolayer coverage are used to determine the nature of the molecule-surface interactions and the molecular orientation. An experimental density of states for the monolayer with respect to the underlying metal surface is obtained by combining x-ray absorption spectroscopy at the N 1s edge and valence photoemission to measure the unoccupied and occupied valence states, respectively. This shows that the lowest unoccupied molecular orbital in the core-excited state lies energetically below the Fermi level of the surface allowing charge transfer from the metal into this orbital. Resonant photoelectron spectroscopy was used to probe this charge transfer in the context of super-spectator and super-Auger electron transitions. The results presented provide a novel interpretation of resonant core-level spectroscopy to explore ultra-fast charge transfer between an adsorbed organic molecule and a metal surface through the observation of electrons from the metal surface playing a direct role in the core-hole decay of the core-excited molecule.